Resin-coated metal sheet
The resin-coated metal plate with a specific three-layer structure and polyolefin dispersion particle size range addresses the challenges of slip resistance, shaving resistance, and ink adhesion, enhancing the durability and aesthetic appeal of metal containers.
Patent Information
- Application Number
- JP2023561109
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-09-06
- Filing Date
- 2023-06-06
- Publication Date
- 2025-05-09
- Estimated Expiration
- 2043-06-06
AI Technical Summary
Existing resin-coated metal plates face challenges in achieving both slip resistance and shaving resistance while maintaining adequate ink adhesion, particularly due to the risk of resin coating layer breakage or peeling during can manufacturing and printing processes.
A resin-coated metal plate with a specific structure, including a resin coating layer composed of at least 75% polyester resin, a three-layer structure with a topmost layer containing polyolefin, and a dispersion particle diameter of polyolefin within a specific range (0.018 μm to 5.0 μm) measured by Raman spectroscopy, ensuring optimal slip resistance, shaving resistance, and ink adhesion.
The proposed solution effectively enhances the slip resistance, shaving resistance, and ink adhesion of the resin-coated layer, preventing breakage or peeling during manufacturing and ensuring improved design and beauty of the can exterior.
Smart Images

Figure 0007673826000004 
Figure 0007673826000001 
Figure 0007673826000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin-coated metal sheet. [Background technology]
[0002] Laminated steel sheets have been developed by covering the surface of metal sheets, such as tin-free steel (TFS) and aluminum, which are used as materials for metal containers, with a thermoplastic resin film. Laminated steel sheets are widely used in the fields of beverage cans and food cans, which require strict forming processing.
[0003] In recent years, in order to conserve resources and reduce material costs, the materials used for metal containers, particularly the metal plate and the resin coating layer, have been made thinner by tightening the processing conditions. This increases the degree of processing during can body production, and there is a possibility that the resin coating layer located on the outer surface side of the container may break or be scraped, especially after molding. In light of this, there is a demand for material design that suppresses breakage or scraping of the resin coating layer during can body production. As a technology for suppressing breakage or scraping of the resin coating layer, Patent Documents 1 and 2 propose a method of adding a lubricating component to the resin coating layer to increase the slipperiness and scraping resistance of the resin coating layer.
[0004] After molding, the resin coating layer located on the outer surface of the container is printed to improve its design. If the affinity between the various inks used for printing and the resin coating layer is low, sufficient ink adhesion cannot be ensured, and the printing ink may peel off during can processing, which may impair the design and beauty of the can's appearance. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2019 / 116706 [Patent Document 2] International Publication No. 2019 / 116707 Summary of the Invention [Problem to be solved by the invention]
[0006] The lubricating component added to the resin coating layer suppresses the breakage or scraping of the resin coating layer. On the other hand, it may inhibit the affinity between the printing ink applied in the printing process and the surface of the resin coating layer, which may cause the ink to peel off during processing. Therefore, a resin-coated metal sheet that can more highly balance the slipperiness and scraping resistance of the resin coating layer with the adhesion of the printing ink is required.
[0007] SUMMARY OF THE PRESENT EMBODIMENTS The present invention has an object to provide a resin-coated metal sheet which has a resin coating layer that is excellent in both slipperiness and abrasion resistance as well as ink adhesion. [Means for solving the problem]
[0008] The present inventors have conducted extensive research to achieve the above-mentioned object, and have come to the following findings. Conventionally, only the dispersed particle size of the lubricating component present locally on the outermost surface of the resin coating layer has been grasped. The present inventors have three-dimensionally grasped the dispersed particle size of the lubricating component present inside the resin coating layer in the thickness direction in a wider range, and have found a dispersed particle size range of the lubricating component that satisfies both the slipperiness, abrasion resistance, and ink adhesion of the resin coating layer, thereby completing the present invention.
[0009] The present invention has been made based on the above findings. That is, the gist and configuration of the present invention are as follows.
[0010] [1] A resin-coated metal sheet having a resin coating layer containing 75% by mass or more of polyester resin on at least one side of a metal sheet, the resin coating layer has at least a three-layer structure including an outermost layer, an intermediate layer, and a bottom layer, The melting point of the resin coating layer is 230° C. or higher and 254° C. or lower, The outermost layer contains a polyolefin, The melting point of the polyolefin is 80° C. or more and 140° C. or less, the dispersed particle diameter of the polyolefin measured by Raman spectroscopy on the outermost surface and inside in the thickness direction of the resin coating layer is 0.018 μm or more and 5.0 μm or less; Resin-coated metal sheet.
[0011] [2] The resin-coated metal sheet according to the above [1], wherein the outermost layer contains 0.10 mass % or more and 1.0 mass % or less of the polyolefin.
[0012] [3] The resin-coated metal sheet according to [1] or [2] above, wherein the weight-average molecular weight of the polyolefin is 2,500 or more and 80,000 or less.
[0013] [4] The resin-coated metal sheet according to any one of the above [1] to [3], wherein the polyolefin is at least one of an acid-modified polyolefin and an oxidized polyolefin.
[0014] [5] The resin-coated metal sheet according to any one of the above [1] to [4], wherein the acid value of the polyolefin is from 1.0 mgKOH / g to 80 mgKOH / g.
[0015] [6] The resin-coated metal sheet according to any one of the above [1] to [5], wherein the intermediate layer contains 10% by mass or more and 30% by mass or less of inorganic particles.
[0016] [7] The resin-coated metal sheet according to any one of [1] to [6] above, wherein the outermost layer and the lowermost layer each have a thickness of 1.0 μm or more and 5.0 μm or less, and the intermediate layer has a thickness of 6.0 μm or more and 30 μm or less.
[0017] [8] A metal container made using the resin-coated metal sheet according to any one of the above [1] to [7], The resin coating layer is located on the outside of the metal container. Effect of the Invention
[0018] According to the present invention, it is possible to provide a resin-coated metal sheet which has a resin coating layer that exhibits both good slip properties, good abrasion resistance, and good ink adhesion. [Brief description of the drawings]
[0019] [Figure 1] FIG. 2 is a schematic diagram showing a cross section of a resin-coated metal sheet. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] Hereinafter, an embodiment of the present invention will be described, however, the present invention is not limited to the following embodiment.
[0021] FIG. 1 is a cross-sectional view showing the configuration of a resin-coated metal sheet according to one embodiment of the present invention. As shown in FIG. 1, the resin-coated metal sheet 1 has a metal sheet 2, a resin coating layer 3 formed on the front surface side of the metal sheet 2, and a resin coating layer 4 formed on the back surface side of the metal sheet 2. The resin coating layers 3 and 4 may be provided on only one side of the metal sheet 2. The resin coating layer 3 and the resin coating layer 4 are located on the outer surface side and the inner surface side of the container, respectively, after molding. In addition, the resin coating layer 3 has at least a three-layer structure consisting of an outermost layer 3a, an intermediate layer 3b, and a bottom layer 3c, as shown in FIG. 1, and the resin coating layer 4 may also have a three-layer structure.
[0022] [Metal plate] The metal plate is preferably a steel plate. The metal plate is preferably tinplate or tin free steel (TFS). For tinplate, the plating weight per side is 0.5 g / m. 2 More than 15g / m 2 It is preferable to use tinplate within the following range: TFS has a coating weight of 50 mg / m2 per side. 2 More than 200mg / m 2 The following metal chrome layer and the metal chrome layer are covered with a metal chrome equivalent coating weight of 3mg / m per side. 2 More than 30mg / m 2It is preferable that the metal plate has a chromium oxide layer on the surface thereof as described below. The type of metal plate is not particularly limited as long as it can be formed into a desired shape, but a metal plate having the components and produced by the method described below is preferable. (1) A metal plate obtained by recrystallization annealing low-carbon steel having a C (carbon) content in the range of 0.010 mass% or more and 0.10 mass% or less using continuous annealing. (2) A metal sheet obtained by subjecting low-carbon steel having a C content in the range of 0.010 mass% or more and 0.10 mass% or less to recrystallization annealing and overaging treatment by continuous annealing. (3) A metal sheet obtained by recrystallization annealing low-carbon steel having a C content in the range of 0.010 mass% or more and 0.10 mass% or less using box annealing. (4) A metal sheet obtained by subjecting low-carbon steel having a C content in the range of 0.010% by mass or more and 0.10% by mass or less to recrystallization annealing by continuous annealing or box annealing, followed by secondary cold rolling (double reduced rolling). (5) A metal sheet obtained by recrystallization annealing IF (Interstitial Free) steel, which is made by adding elements that fix the dissolved C, such as Nb and Ti, to ultra-low carbon steel with a C content of 0.003 mass% or less, through continuous annealing.
[0023] The mechanical properties of the steel sheet are not particularly limited as long as they can be formed into a desired shape. In order to obtain more suitable workability and to maintain more suitable can body strength, the yield point (YP) of the steel sheet is preferably 220 MPa or more and preferably 580 MPa or less. In addition, the steel sheet preferably has a Lankford value (r value), which is an index of plastic anisotropy, of 0.8 or more. Furthermore, the steel sheet preferably has an absolute value of 0.7 or less for the in-plane anisotropy Δr of the r value.
[0024] The components of the steel to satisfy the above mechanical properties are not particularly limited, but may contain, for example, components such as Si, Mn, P, S, Al, and N. The Si content is preferably 0.001 mass% or more, and preferably 0.1 mass% or less. The Mn content is preferably 0.01 mass% or more, and preferably 0.6 mass% or less. The P content is preferably 0.002 mass% or more, and preferably 0.05 mass% or less. The S content is preferably 0.002 mass% or more, and preferably 0.05 mass% or less. The Al content is preferably 0.005 mass% or more, and preferably 0.100 mass% or less. The N content is preferably 0.0005 mass% or more, and preferably 0.020 mass% or less. The steel sheet may contain other components such as Ti, Nb, B, Cu, Ni, Cr, Mo, and V, but from the viewpoint of ensuring corrosion resistance, etc., the total content of these component elements is preferably 0.02 mass% or less.
[0025] The thickness of the metal plate is not particularly limited, but may be, for example, 0.20 mm or more and 0.25 mm or less.
[0026] [Resin coating layer] The resin coating layer 3 contains polyester resin in an amount of 75% by mass or more, calculated as solid content, based on the total resin. The content of polyester resin here refers to the proportion of polyester resin in the resin, minus the weight of additives such as polyolefin and inorganic particles contained in the resin coating layer. The resin coating layer 3 preferably contains polyester resin in an amount of 80% by mass or more, and preferably 100% by mass or less, based on the total resin.
[0027] The polyester resin is a polymer composed of dicarboxylic acid units and glycol units.
[0028] As the dicarboxylic acid unit, there can be used units derived from aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, naphthalenedicarboxylic acid, diphenyldicarboxylic acid, diphenylsulfonedicarboxylic acid, diphenoxyethanedicarboxylic acid, 5-sodiumsulfoisophthalic acid, and phthalic acid; aliphatic dicarboxylic acids such as oxalic acid, succinic acid, adipic acid, sebacic acid, dimer acid, maleic acid, and fumaric acid; alicyclic dicarboxylic acids such as cyclohexanedicarboxylic acid; and oxycarboxylic acids such as p-oxybenzoic acid.
[0029] As the glycol unit, units derived from aliphatic glycols such as ethylene glycol, propanediol, butanediol, pentanediol, hexanediol, and neopentyl glycol; alicyclic glycols such as cyclohexanedimethanol; aromatic glycols such as bisphenol A and bisphenol S; and diethylene glycol can be used.
[0030] The above dicarboxylic acids and glycols may be used in combination in two or more amounts as long as the heat resistance and processability are not impaired.
[0031] The resin coating layer 3 has a melting point of 230°C or more and 254°C or less. If the melting point of the resin coating layer 3 is 230°C or more, the resin can be suitably prevented from softening during molding, and the occurrence of breakage or scraping can be more suitably prevented. If the melting point of the resin coating layer 3 is 254°C or less, the crystallinity of the polyester resin contained is in a more suitable range, and the occurrence of breakage or scraping in the resin coating layer 3 during molding can be more suitably prevented. The melting point of the resin coating layer 3 is preferably 234°C or more, and more preferably 238°C or more. The melting point of the resin coating layer 3 is preferably 252°C or less, and more preferably 250°C or less. The melting point of the resin coating layer 3 is measured according to the following method. The resin coating layer 3 is measured using a differential scanning calorimeter, and the peak top temperature of the endothermic peak in the range of 200°C to 280°C in the obtained heat flow is taken as the melting point.
[0032] Of the resin coating layer 3, the outermost layer 3a contains polyolefin as a lubricating component. By containing polyolefin as a lubricating component in the outermost layer 3a, excellent slip properties and abrasion resistance can be ensured, and breakage or abrasion of the resin coating layer 3 can be suppressed even in can body molding under severe processing conditions. As the lubricating component, a polyolefin having excellent film-forming and dispersibility and a melting point within an appropriate range is used. Preferably, a polyolefin having a polar group is used to ensure sufficient affinity with the polyester resin, which is the main component of the resin coating layer 3. Examples of polyolefins having a polar group include acid-modified polyolefins such as ethylene-maleic anhydride copolymers, oxidized polyolefins such as polyethylene oxide, and ethylene-acrylic acid copolymers. As the polyolefin, a combination of multiple types of polyolefins may be used.
[0033] The polyolefin is preferably at least one of an acid-modified polyolefin and an oxidized polyolefin. When the polyolefin is at least one of an acid-modified polyolefin and an oxidized polyolefin, the acid value becomes sufficiently high, and the affinity between the outermost layer 3a and the printing ink is improved. The polyolefin may be a mixture of an acid-modified polyolefin and an oxidized polyolefin.
[0034] The melting point of the polyolefin is 80°C or more and 140°C or less. If the melting point of the polyolefin is less than 80°C, the polyolefin is likely to thicken on the surface of the resin coating layer 3 due to the heat treatment performed during the process of coating the resin coating layer 3 on the metal plate and during the molding process of the resin-coated metal plate. The polyolefin thickened on the surface inhibits the adhesion of the printing ink, and there is a possibility that the printing ink will peel off during the molding process. In addition, if the melting point of the polyolefin exceeds 140°C, sufficient slip properties and abrasion resistance cannot be ensured, and there is a possibility that the resin coating layer 3 will break or be abraded during the molding process. The melting point of the polyolefin is preferably 90°C or more, more preferably 100°C or more. The melting point of the polyolefin is preferably 130°C or less, more preferably 120°C or less. The melting point of the polyolefin is measured according to the method described in the examples below.
[0035] The dispersed particle size of the polyolefin on the outermost surface and inside in the thickness direction of the resin coating layer 3 is 0.018 μm or more and 5.0 μm or less. The dispersed particle size of the polyolefin is measured by peak intensity ratio analysis of the Raman spectrum obtained by Raman spectroscopy using a confocal Raman spectrometer. This measurement method makes it possible to calculate the dispersion state of the polyolefin in the resin coating layer 3 nondestructively and three-dimensionally with high resolution, and it is possible to capture the dispersed particle size of the polyolefin that cannot be captured by other analysis methods. If the dispersed particle size of the polyolefin present on the outermost surface and inside in the thickness direction of the resin coating layer 3 is less than 0.018 μm, it is extremely small, so sufficient slipperiness and abrasion resistance cannot be ensured, and there is a risk of breakage or abrasion during molding. In addition, if the dispersed particle size of the lubricating component present on the outermost surface and inside in the thickness direction of the resin coating layer 3 exceeds 5.0 μm, there is a possibility that breakage or abrasion will occur due to excessively large dispersed particles of polyolefin as the starting point during molding. In addition, due to the influence of multiple heat treatments performed during molding, the proportion of polyolefins that are concentrated and exposed on the surface of the resin coating layer 3 increases, hindering the adhesion of the printing ink and possibly causing the printing ink to peel off during molding. The dispersed particle size of the polyolefin on the outermost surface and inside in the thickness direction of the resin coating layer 3 is preferably 0.030 μm or more, more preferably 0.050 μm or more. The dispersed particle size of the polyolefin on the outermost surface and inside in the thickness direction of the resin coating layer 3 is preferably 3.0 μm or less, more preferably 2.0 μm or less, and even more preferably 1.0 μm or less. The dispersed particle size of the polyolefin on the outermost surface and inside in the thickness direction of the resin coating layer 3 is measured according to the method described in the Examples below.
[0036] Conventional methods for measuring the dispersed particle size of lubricating components include a method using a chemical force microscope (CFM). In this method, only the surface of the resin coating layer is observed in a field area of 1 μm × 1 μm, and the dispersed particle size of the observed lubricating component particles is calculated from the major and minor diameters. On the other hand, when using Raman spectroscopy as in the present invention, a field of view of 50 μm (lamination direction of the resin-coated metal sheet) × 50 μm (direction perpendicular to the lamination direction within the plate surface of the resin-coated metal sheet) × 3 μm (thickness direction of the resin-coated metal sheet), which is wider than the conventional method and also includes the thickness direction, is measured, and the dispersed particle size is calculated. Therefore, Raman spectroscopy can capture more dispersed particles of polyolefin in the resin coating layer than the conventional method, and a highly accurate dispersed particle size can be obtained.
[0037] Furthermore, as another conventional method, there is a method in which the polyester resin of the surface layer of the resin coating layer is etched with an alkaline aqueous solution, and the major and minor diameters of the remaining modified polyolefin particles are measured one by one to calculate the particle size. This method is a destructive measurement, and the dispersion state of the modified polyolefin particles actually dispersed in the resin coating layer cannot be captured. In addition, when the resin coating layer is etched with an alkaline aqueous solution, the shape and particle size of the extracted modified polyolefin particles may differ from the state in which they are dispersed in the resin coating layer. Therefore, it is difficult to determine how much the modified polyolefin particles contribute to the required performance of the resin coating layer or the resin-laminated metal sheet by this method. On the other hand, when Raman spectroscopy is used as in the present invention, the particle size and dispersion state of the polyolefin actually dispersed in the resin coating layer can be captured non-destructively and with high resolution, so that it is possible to determine how much the dispersed particles of the polyolefin contribute to the required performance with high accuracy.
[0038] The content of polyolefin in the outermost layer 3a is preferably 0.10% by mass or more, and preferably 1.0% by mass or less, calculated as solid content. If the content of polyolefin in the outermost layer 3a is 0.10% by mass or more, more suitable slip properties and abrasion resistance can be ensured during molding, and breakage or abrasion of the resin coating layer 3 can be prevented. If the content of polyolefin in the outermost layer 3a is 1.0% by mass or less, abrasion resistance and ink adhesion are more suitable. The content of polyolefin in the outermost layer 3a is more preferably 0.20% by mass or more, and even more preferably 0.40% by mass or more. The content of polyolefin in the outermost layer 3a is more preferably 0.90% by mass or less, and even more preferably 0.80% by mass or less.
[0039] The weight average molecular weight of the polyolefin is preferably 2500 or more, and preferably 80000 or less. If the weight average molecular weight of the polyolefin is 2500 or more, the polyolefin can be more preferably prevented from thickening on the surface of the resin coating layer 3, and the ink adhesion can be more preferably improved. If the weight average molecular weight of the polyolefin is 80000 or less, more preferable slip properties and abrasion resistance can be secured during molding processing, and the resin coating layer 3 can be more preferably prevented from being broken or abraded. The weight average molecular weight of the polyolefin is more preferably 3000 or more, and even more preferably 3500 or more. The weight average molecular weight of the polyolefin is more preferably 70000 or less, and even more preferably 65000 or less. The weight average molecular weight of the polyolefin is measured according to the method described in the Examples below.
[0040] The acid value of the polyolefin is preferably 1.0 mgKOH / g or more, and preferably 80 mgKOH / g or less. If the acid value of the polyolefin is 1.0 mgKOH / g or more, the affinity between the resin coating layer 3 and the printing ink can be sufficiently ensured, and the adhesion of the printing ink can be improved. If the acid value of the polyolefin is 80 mgKOH / g or less, the resin coating layer 3 is not compatible with the polyolefin, so that more suitable slip properties and abrasion resistance can be ensured, and breakage or abrasion during molding can be more suitably prevented. The acid value of the polyolefin is more preferably 1.5 mgKOH / g or more, and even more preferably 2.0 mgKOH / g or more. The acid value of the polyolefin is more preferably 50 mgKOH / g or less, and even more preferably 45 mgKOH / g or less. The acid value of the polyolefin is measured according to the method described in the Examples below.
[0041] The resin coating layer 3 may be required to be white in order to improve the design and beauty of the exterior appearance of the can body after printing. In this case, it is preferable that the intermediate layer 3b of the resin coating layer 3 contains inorganic particles. This is because the resin coating layer 3 can be made white by containing inorganic particles in the intermediate layer 3b.
[0042] The intermediate layer 3b preferably contains 10% by mass or more, and more preferably 30% by mass or less, of inorganic particles calculated as solid content. If the intermediate layer 3b contains 10% by mass or more of inorganic particles, sufficient whiteness can be ensured. If the intermediate layer 3b contains 30% by mass or less of inorganic particles, breakage or scraping of the resin coating layer 3 can be more suitably prevented even under more severe processing conditions. The content of inorganic particles in the intermediate layer 3b is more preferably 12% by mass or more, and even more preferably 15% by mass or more. The content of inorganic particles in the intermediate layer 3b is more preferably 25% by mass or less, and even more preferably 20% by mass or less.
[0043] The inorganic particles contained in the intermediate layer 3b are not particularly limited. The inorganic particles are preferably titanium oxide. The titanium oxide is preferably rutile type titanium oxide having a purity of 90% or more. When the inorganic particles contained in the intermediate layer 3b are the above-mentioned titanium oxide, the titanium oxide exhibits good dispersibility when mixed with the polyester resin, and the design and beauty of the appearance are improved with a uniform whiteness.
[0044] When the resin coating layer 3 has at least a three-layer structure consisting of the outermost layer 3a, the intermediate layer 3b, and the bottom layer 3c, the thicknesses of the outermost layer 3a and the bottom layer 3c are preferably 1.0 μm or more and 5.0 μm or less, respectively. The thicknesses of the outermost layer 3a and the bottom layer 3c may be different from each other. By having the thicknesses of the outermost layer 3a and the bottom layer 3c within the above range, more suitable slip properties and abrasion resistance can be ensured during molding processing, and the resin coating layer 3 can be more suitably prevented from being broken or abraded. The thicknesses of the outermost layer 3a and the bottom layer 3c are more preferably 1.5 μm or more, and more preferably 2.0 μm or more, respectively. The thicknesses of the outermost layer 3a and the bottom layer 3c are more preferably 4.0 μm or less, and more preferably 3.0 μm or less, respectively. The thicknesses of the outermost layer 3a and the bottom layer 3c are measured according to the method described in the Examples below.
[0045] The thickness of the intermediate layer 3b is preferably 6.0 μm or more, and preferably 30 μm or less. When the thickness of the intermediate layer 3b is within the above range, there is no need to vary the thicknesses of the outermost layer 3a and the bottom layer 3c, and the increase or decrease in the absolute amount of polyolefin is suppressed. Therefore, the dispersed particle size falls within a more appropriate range, and the resin coating layer 3 can be more suitably prevented from being broken or scraped during molding. In addition, the adhesion of the printing ink to the resin coating layer 3 can be further improved. The thickness of the intermediate layer 3b is more preferably 8.0 μm or more, and more preferably 10 μm or more. The thickness of the intermediate layer 3b is more preferably 25 μm or less, and more preferably 20 μm or less. The thickness of the intermediate layer 3b is measured according to the method described in the Examples below.
[0046] The outermost layer 3a and the bottom layer 3c preferably contain 95% by mass or more and 100% by mass or less of polyester resin in terms of solid content. The intermediate layer 3b preferably contains 70% by mass or more and 100% by mass or less of polyester resin in terms of solid content. The content of polyester resin here refers to the proportion of polyester resin in the resin, minus the weight of additives such as polyolefin contained in the resin coating layer 3.
[0047] By using the above-mentioned resin-coated metal sheet, it is possible to manufacture a metal container that satisfies both the slipperiness and abrasion resistance of the resin coating layer 3 and the ink adhesion. The metal container can be manufactured by a conventional method.
[0048] Next, an example of a method for producing a resin-coated metal sheet will be described. In one example, a resin film having at least a three-layer structure including a top layer, an intermediate layer, and a bottom layer is pressure-bonded to at least one side of the metal sheet to form a resin coating layer 3. After pressure-bonding to the metal sheet, the top layer, the intermediate layer, and the bottom layer become the top layer 3a, the intermediate layer 3b, and the bottom layer 3c, respectively.
[0049] In the manufacture of the resin-coated metal plate, a resin film to be pressure-bonded to the metal plate is manufactured first. The manufacturing method of the resin film is not particularly limited. In one example, first, in order to incorporate polyolefin into the outermost film, polyolefin is added to a resin containing polyester resin at 75% by mass or more relative to the total resin. The method of adding polyolefin to the resin is not particularly limited, but a method using a master batch in which polyolefin is dispersed in a high concentration in the resin using a kneading extruder is preferred. During film formation, the resin pellets and the master batch are mixed at a predetermined ratio and introduced into the kneading extruder. When mixing the resin pellets and the master batch, it is preferable to set the extrusion temperature to a temperature higher than the melting point of the resin pellets. In one example, it is preferable to perform mixing at an extrusion temperature of 260°C or higher, which is 30°C higher than the melting point of the polyester resin. In addition, the extrusion temperature is preferably 284°C or lower. In order to control the dispersed particle size of the polyolefin, it is more preferable to set the extrusion temperature to 265°C or higher. In order to control the dispersed particle size of the polyolefin, the screw speed of the extruder is preferably set to 12 rpm or more and 18 rpm or less. In addition, inorganic particles may be appropriately mixed into the resin that becomes the interlayer.
[0050] In one example, a mixture of a resin and a polyolefin that will be the top layer, a resin that will be the intermediate layer, and a resin that will be the bottom layer are co-extruded, formed into a sheet shape using a T-die, and discharged onto a cooling body such as a cast drum. The extruded sheet is cooled and solidified to obtain a non-stretched laminated film.
[0051] After the non-stretched laminated film is produced, it is preferably stretched in biaxial directions once in the film-forming direction and once in the direction perpendicular to the film-forming direction to produce a resin film. Furthermore, in order to control the dispersed particle size of polyolefin, the stretching ratio after the non-stretched laminated film is preferably 2.0 times or more, more preferably 3.0 times or more. The stretching ratio after the non-stretched laminated film is preferably 5.0 times or less, more preferably 4.5 times or less.
[0052] The produced resin film is heated above its melting point and pressed onto a metal plate using a lamination roll (thermocompression film lamination method). This thermocompression film lamination method is advantageous in that it keeps production costs down and allows for energy-saving production.
[0053] The production conditions other than those mentioned above can be the same as those in the ordinary methods. EXAMPLES
[0054] The plate thickness is 0.22 mm, and the metal chromium layer is 120 mg / m per side. 2 , the chromium oxide layer is 10mg / m per side in terms of metallic chromium 2 A TFS having a temper of T3CA was used as the metal plate. The mechanical properties of the metal plate were YP of 400 MPa, r value of 1.0, and Δr of 0.5. A resin film having a three-layer structure was formed by biaxial stretching using the resin, polyolefin, and titanium oxide shown in Tables 1 and 2. The resin coating layer used in the present embodiment and the comparative example was a resin coating layer containing 100% by mass of polyester resin relative to the total resin, and the resin composition is shown in Tables 1 and 2. The metal plate was heated, and a resin film was thermocompression-bonded to both the front and back sides of the metal plate by a thermocompression film lamination method. After 1.5 seconds had elapsed since the thermocompression bonding, the resin coating layers of the invention examples 1 to 22 and the comparative examples 1 to 8 were coated on both sides of the metal plate by water cooling in a water-cooled tank. The outermost layer contained polyolefin in the amount shown in Tables 1 and 2. The intermediate layer contained titanium oxide in the amount shown in Tables 1 and 2. The coating conditions were as shown in Tables 1 and 2 below. In addition, paraffin wax was added instead of polyolefin in Comparative Example 7. The item for Comparative Example 7 in Table 2 shows the amount of paraffin wax added, the melting point, the weight average molecular weight, and the dispersed particle size.
[0055] For the resin-coated metal sheets produced by the above method, the melting point of the resin coating layer and the melting point of the polyolefin, the dispersed particle size of the polyolefin present on the outermost surface and inside of the resin coating layer, the weight average molecular weight of the polyolefin, the acid value of the polyolefin, and each layer thickness of the resin coating layer were analyzed by the methods described below.
[0056] (1) Melting point of the resin coating layer First, the resin-coated metal plate for containers was immersed in a mixed solution of concentrated hydrochloric acid (30 wt%) and distilled water = 1:1 at room temperature, and the resin coating layer was peeled off by dissolving the metal plate. Using a differential scanning calorimeter: DSCQ100 manufactured by TA Instruments, the peeled resin coating layer was measured under the conditions of atmospheric gas of N2, flow rate of 50 ml / min, temperature range from room temperature to 290 °C, and heating rate of 10 °C / min. The peak top temperature of the endothermic peak in the range of 200 °C to 280 °C in the obtained heat flow was taken as the melting point.
[0057] (2) Melting point of polyolefin After peeling off the resin coating layer from the resin-coated metal plate in the same manner as in (1), the resin coating layer was dissolved using hexafluoro-2-propanol (HFIP) as a solvent. The dissolved resin coating layer was centrifuged and then pressure-filtered with filters having pore sizes of 1 μm and 0.1 μm in sequence to extract the polyolefin contained in the outermost layer of the resin coating layer. In addition, Soxhlet extraction was performed on the above filter using xylene as a solvent to extract additional polyolefin after concentration, reprecipitation, and centrifugation. The lubricating components extracted as described above were measured using a differential scanning calorimeter: DSCQ100 manufactured by TA Instruments under the conditions of N2 atmosphere gas, flow rate of 50 ml / min, temperature range from room temperature to 290 ° C, and heating rate of 10 ° C / min. The peak top temperature of the endothermic peak in the range of 70 ° C to 150 ° C of the obtained heat flow was taken as the melting point.
[0058] (3) Dispersion particle size of polyolefin present on the outermost surface and inside of the resin coating layer Using a microscopic laser Raman spectrometer (LabRAM HR VIS-NIR) manufactured by Horiba Ltd., the surface of a resin-coated metal plate was measured with a confocal laser at the following conditions: laser power 10%, aperture 25 μm, exposure time 0.08 sec, exposure count 1, grating 300 lines / mm, objective lens 100x, wave number range 310-3400 cm -1The Raman spectrum was measured by Raman spectroscopy under the following conditions. The measurement range was 50 μm (lamination direction of the resin-coated metal plate) × 50 μm (direction perpendicular to the lamination direction within the plate surface of the resin-coated metal plate) × 3 μm (thickness direction of the resin-coated metal plate). The measurement pitch was 0.5 μm in all of the lamination direction, the plate surface direction perpendicular to the lamination direction, and the thickness direction. Based on the obtained Raman spectrum data, a CH stretching vibration peak (2850 cm) derived from polyethylene was detected. -1 ) and the CH stretching vibration peak (2960 cm ) derived from polyester, the main component of the resin coating layer. -1 ) was calculated and mapped to calculate the major axis of the dispersed particles of each polyolefin. Three fields of view were randomly selected for each sample, and measurements were performed on all dispersed particles of polyolefin within the measurement fields.
[0059] (4) Weight average molecular weight of polyolefin Using an Agilent gel permeation chromatograph analyzer: PL-GPC220, the polyolefin extracted in the same manner as in (2) was measured under the conditions of Agilent PLgel Olexis x 2 + Guard columns and o-dichlorobenzene eluent. A calibration curve was also created from the molecular weight and elution time of standard polystyrene. Using the calibration curve, the weight average molecular weight of the polyolefin was calculated based on the elution time of the polyolefin.
[0060] (5) Acid value of polyolefin The acid value of the polyolefin extracted in the same manner as in (2) was measured in accordance with JIS K5902. A predetermined amount of polyolefin corresponding to the estimated acid value in accordance with JIS K5902 was weighed into a flask and dissolved in 100 ml of a neutral solvent, and then titrated with 0.1 mol / L potassium hydroxide standard solution using phenolphthalein as an indicator. The point at which the color of the indicator changed for 30 seconds was regarded as the end point of neutralization, and the acid value was calculated by the following formula. (Acid value)=5.611×A×F / B A: 0.1 mol / L potassium hydroxide standard solution (ml) B: Sample collection amount (g) F: Factor of 0.1 mol / L potassium hydroxide standard solution
[0061] (6) Thickness of each resin coating layer After peeling off the resin coating layer from the resin-coated metal plate in the same manner as in (1), a Pt coating was applied to the outermost surface of the resin coating layer, and a cross section was prepared using an ion milling device: EM TIC 3X manufactured by Leica Microsystems, Inc. For the prepared cross section, backscattered electron images were observed at two observation magnifications of 2500x and 8000x using a scanning electron microscope (SEM): Regulus 8220 manufactured by Hitachi High-Technologies Corporation, and the thicknesses of the outermost layer, middle layer, and bottom layer of the resin coating layer were calculated from the observed images.
[0062] The resin-coated metal sheets of the above-mentioned invention examples 1 to 22 and comparative examples 1 to 8 were evaluated for lubricity, abrasion resistance, and ink adhesion of the resin coating layer by the methods described below. The evaluation results are shown in Table 3.
[0063] (7) Evaluation of slipperiness and abrasion resistance The resin-coated metal plates of Examples 1 to 22 and Comparative Examples 1 to 8 were punched out into a circular shape with a diameter of 68 mm, and a sliding test was carried out using a rotary abrasion tester manufactured by Takachiho Seiki Co., Ltd., with a super steel ball indenter (Φ10 mm) under the conditions of a load of 44 N, a sample temperature of 145±3°C, a rotation speed of 370 rpm, and a rotation radius of 20 mm. Four tests were carried out for each sample, and the sliding properties were evaluated from the obtained friction coefficient, and the abrasion resistance was visually evaluated from the degree of abrasion of the resin coating layer after the test.
[0064] Evaluation criteria for slipperiness Rating: Good: Friction coefficient is 0.135 or less. Evaluation: △: Friction coefficient is greater than 0.135 and less than 0.160. Rating "x": Friction coefficient is 0.160 or more.
[0065] Evaluation criteria for abrasion resistance Evaluation: "Good": No abrasion was observed visually in all four test samples. Evaluation "△": Scraping was visually observed in one of four test samples. Evaluation "x": Scraping was visually observed in two or more of the four test samples.
[0066] (8) Evaluation of ink adhesion The resin-coated metal sheets of the invention examples 1 to 22 and the comparative examples 1 to 8 were subjected to a heat treatment in a hot air drying oven to reach 240°C in 2 minutes, and then cooled to room temperature. After that, for each sample after the heat treatment, a polyester-based printing ink (red color) was printed on the resin coating layer using a universal printing tester manufactured by Kumagai Riki Kogyo Co., Ltd., and a heat treatment was performed in a hot air drying oven to reach 180°C in 1 minute, and then cooled to room temperature. A scratch test was performed on the ink-printed surface of the obtained sample in the lamination direction of the sample using a load-varying friction and wear tester: HHS2000 manufactured by Shinto Scientific Co., Ltd., under the conditions of a continuous load of 10 to 500 gf from the printing end, a moving speed of 0.5 mm / sec, and a moving distance of 30 mm, using a sapphire indenter (Φ0.6 mm). Ten tests (2 sheets x 5 tests) were performed for each sample, and the ink peeling load was calculated from the obtained ink peeling length to evaluate the ink adhesion. [Ink adhesion evaluation criteria] Evaluation: "Good": The average peel load was 100g or more. Evaluation "△": The average peel load was 80 g or more and less than 100 g. Evaluation: "X": The average peel load was less than 80 g.
[0067] [Table 1]
[0068] [Table 2]
[0069] [Table 3] [Explanation of symbols]
[0070] 1 Resin-coated metal plate 2 Metal plate 3 Resin coating layer 3a Outermost layer 3b Intermediate layer 3c Lowermost layer 4 Resin coating layer
Claims
1. A resin-coated metal plate having a resin coating layer containing 100% by mass of polyester resin on at least one surface of a metal plate, the resin coating layer has at least a three-layer structure including an outermost layer, an intermediate layer, and a bottom layer, The thickness of the outermost layer is 0.8 μm or more and 7.5 μm or less, The thickness of the intermediate layer is 5.5 μm or more and 30 μm or less, The thickness of the bottom layer is 1.0 μm or more and 7.0 μm or less, The melting point of the resin coating layer is 230° C. or higher and 254° C. or lower, The outermost layer contains a polyolefin, The melting point of the polyolefin is 80° C. or more and 140° C. or less, The content of the polyolefin is 0.05% by mass or more and 2.0% by mass or less in terms of solid content, The weight average molecular weight of the polyolefin is 2,000 or more and 85,000 or less, The acid value of the polyolefin is 0.0 mgKOH / g or more and 90 mgKOH / g or less, the dispersed particle size of the polyolefin measured by Raman spectroscopy on the outermost surface and inside in the thickness direction of the resin coating layer is 0.018 μm or more and 5.0 μm or less; Resin-coated metal sheet.
2. The resin-coated metal sheet according to claim 1 , wherein the outermost layer contains 0.10 mass % or more and 1.0 mass % or less of the polyolefin.
3. 2. The resin-coated metal sheet according to claim 1, wherein the polyolefin has a weight average molecular weight of 2,500 or more and 80,000 or less.
4. The resin-coated metal sheet according to claim 1 , wherein the polyolefin is at least one of an acid-modified polyolefin and an oxidized polyolefin.
5. The resin-coated metal sheet according to claim 1, wherein the acid value of the polyolefin is from 1.0 mgKOH / g to 80 mgKOH / g.
6. The resin-coated metal sheet according to claim 1 , wherein the intermediate layer contains 10% by mass or more and 30% by mass or less of inorganic particles.
7. 2. The resin-coated metal sheet according to claim 1, wherein the outermost layer and the lowermost layer each have a thickness of 1.0 μm or more and 5.0 μm or less, and the intermediate layer has a thickness of 6.0 μm or more and 30 μm or less.
8. A metal container made using the resin-coated metal sheet according to any one of claims 1 to 7, The resin coating layer is located on the outside of the metal container.
Citation Information
Patent Citations
Resin coated metal plate for containers
WO2019116706A1
Resin coated metal plate for containers
WO2019116707A1